A221 CROHN'S DISEASE POLYGENIC RISK SCORE IS ASSOCIATED WITH FECAL CALPROTECTIN CONCENTRATION IN ASYMPTOMATIC FIRST-DEGREE RELATIVES OF CROHN'S DISEASE PATIENTS. (26th February 2020) - Lee, S; Shestopaloff, K; Espin-Garcia, O; Turpin, W; Raygoza Garay, J; Power, N; Smith, M; Silverberg, M; Xu, W; Paterson, A D; Croitoru, K
Abstract: Background: Fecal calprotectin concentration (FC), a measure of gut inflammation is reported to be significantly higher in healthy first-degree relatives (FDR) of Crohn's disease (CD) patients compared to healthy controls. In contrast, FC in spouses of CD patients was not significantly different from controls, suggesting that a genetic predisposition rather than a shared environmental factor affects FC. Aims: We investigated the genetic association with FC in healthy FDRs of CD patients. Notably, these subjects are known to be enriched with CD risk alleles. Methods: We investigated 1455 healthy Caucasian FDRs of CD patients from the GEM Project. Subjects were genotyped by HumanCoreEXOME chip and ImmunoChip platforms and then imputed by the Haplotype Reference Consortium v1.1 panel (Michigan Imputation Server). SNPs with a minor allele frequency<5% were removed. FC was measured using BUHLMANN ELISA kit. Heritability was estimated using a pedigree based SOLAR program and a SNP-based GCTA software. Genome wide association of FC was tested using the GEE framework that accounts for family clusters, age, sex, first 3 genetic principal components and multiplex family status (≥2 FDRs diagnosed with CD). In addition, CD-polygenic risk scores were derived based on summary statistics and imputed SNPs from a recent GWAS by pruning and thresholding (P+T) and LDPred algorithm (PMID:31002795). Results: Among 1455 subjects, 45.2% were male, median age was 19 years (IQR 13–26), 8.8% were from multiplex families, and median FC was 52 mg/kg (IQR 31–87; 20.8% had FC>100). We estimated the heritability of FC to be 27% (27.1%, standard error=9%, p<0.001 by pedigree approach; 27.9%, SE=12%, p<0.001 by SNP approach). An untargeted GWAS failed to show any significant association with FC (i.e. p<5x10 -8 ). The lowest p value was obtained for rs224631 (p=5x10 -7 ). Strikingly, an increase in CD polygenic risk scores was significantly associated with an increase of FC (p=5.2x10 -5 with P+T method). Conclusions: We demonstrate that FC concentration is a heritable trait in unaffected FDRs of CD patients. Although the association between genetic variants with FC did not reach GWAS significance, CD-polygenic risk score, which incorporates small effect size CD-associated SNPs, was significantly associated with FC concentrationin this cohort. Our results suggest that FC concentration is influenced genetically with contributions from CD-associated SNPs in unaffected FDRs of CD probands. It remains to be determined if the genetic influence to FC concentration is dependent/independent with the future development of CD. Submitted on behalf of The CCC-GEM Project research team Funding Agencies: CCCHelmsley Charitable Trust/ Mount Sinai Hospital Fellowship Award